Impact of Workload and Work Environment on Cyberloafing Behavior - Nurhasanah; Kiki Wulandari; Asmaul Husna (Journal of Research in Business, Economics, and Education, 2021)
This study aims to explain how much workload and work environment on cyberloafing behavior. At this time the internet has become a necessity for humans to facilitate and accelerate the delivery of information or receive information from various sources. Internet users in Indonesia continue to increase. The internet can be easily accessed by anyone and anywhere, including at work. The internet is very helpful for companies in achieving their goals more effectively and efficiently, both in terms of cost, effort, and time. Almost all offices/companies are equipped with wifi or PC facilities that are directly connected to the internet so that employees are greatly assisted in completing their work. On the other hand, facilities in the workplace in the form of easy internet access can cause problems if employees cannot use them optimally to help complete their work.